(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In This paper, we introduce the concept of a left fixed map in a KU-algebra and we discuss some related properties of this concept. Moreover, we study the notion of leftright (resp., right-left) -derivation in a KU-algebra and establish some results on - derivation in a KU-algebra.